Penelitian Market Terhadap Konsep Bisnis Kerajinan Pepakatto - Kezia Lauren Handoyo; Christian Anggrianto (Jurnal Vicidi, 2019)
Market research on the concept of the Pepakatto handicraft business was conducted with the aim of evaluating and developing the Pepakatto business, namely selling interior products in the form of lamps made from paper layering techniques. The purpose of making this business idea is due to the problem of not being able to sleep with the lights off experienced by not only young children, but also teenagers and adults. The research method used is using qualitative methods, namely interviews, and quantitative methods, namely the distribution of questionnaires. The conclusion of the research results obtained are teenagers and young people or young adults who have just had a family.